Accumulation of pollutants in nestlings of an endangered avian scavenger related to territory urbanization and physiological biomarkers. (September 2019) - Ortiz-Santaliestra, Manuel E.; Tauler-Ametller, Helena; Lacorte, Silvia; Hernández-Matías, Antonio; Real, Joan; Mateo, Rafael
Abstract: We monitor pollutant accumulation and investigate associated changes at the physiological level within the population of an obligate avian scavenger, the Egyptian Vulture ( Neophron percnopterus ), from Catalonia (NE Spain). This population is expanding its range, presumably because of the use of human waste disposal sites as food resource. We hypothesized that habitat urbanization, presumably associated with feeding from human wastes, could influence the accumulation of persistent organic pollutants and metals. The aim of this study was to explore the relationship between accumulated pollutants and biochemical parameters in nestling blood. We used the proportion of urban surface within an 8 km radius of each nest as a proxy to study the relationship between anthropic influence and pollutant accumulation. Observed blood levels of metals, organochlorine pesticides, polychlorinated biphenyls (PCBs), per- and polyfluoroalkylated substances (PFAS) and polybrominated diphenyl ethers (PBDEs) were relatively low, as expected for nestling individuals due to short-term exposures. CB-180 and PBDEs were associated with variations in blood biochemistry parameters; hexa-BDEs appeared positively associated with activities of the enzymes aspartate aminotransferase and lactate dehydrogenase, whereas CB-180 accumulation was associated with an increased activity of creatine phosphokinase and elevated glutathione levels. Increased CB-180 levels were also related to decreased blood concentrations of calcium, cholesterol, α-tocopherol and lutein. A proportion of urban surfaces as low as 6.56% within a radius of 8 km around the nest appears related to the accumulation of CB-180, the majority of analysed PFAS and of PBDE congeners 99 and 209, and increased urbanization was also associated with decreased plasma levels of α-tocopherol and carotenoids. These associations suggest that changes in blood profiles of vitamins, carotenoids or other analytes, despite related to increased plasma levels of CB-180, would be consequence of exploitation of artificial food sources rather than of a direct effect of the pollutants. Graphical abstract: Image 1 Highlights: POP and metal accumulation was analysed in Egyptian Vulture nestlings. Associations of pollutants with physiology and land urbanization were studied. Nestlings from the more urbanized territories showed higher plasma levels of POPs. The main determinants of physiological status were CB-180 and PBDEs. CB-180 related to altered nutrition, possibly because feeding from human waste. Abstract : Accumulation of POPs in nestlings of the endangered Egyptian vulture associates with territory urbanization.